Nonlinear Dynamics and Analysis of a Planar Multilink Complex Mechanism with Clearance - Xiulong Chen; Shuai Jiang; Yu Deng; Qing Wang (Shock and Vibration)
In order to understand the nonlinear dynamic behavior of a planar mechanism with clearance, the nonlinear dynamic model of the 2-DOF nine-bar mechanism with a revolute clearance is proposed; the dynamic response, phase diagrams, Poincaré portraits, and largest Lyapunov exponents (LLEs) of mechanism are investigated. The nonlinear dynamic model of 2-DOF nine-bar mechanism containing a revolute clearance is established by using the Lagrange equation. Dynamic response of the slider’s kinematics characteristic, contact force, driving torque, shaft center trajectory, and the penetration depth for 2-DOF nine-bar mechanism are all analyzed. Chaos phenomenon existed in the mechanism has been identified by using the phase diagrams, the Poincaré portraits, and LLEs. The effects of the different clearance sizes, different friction coefficients, and different driving speeds on dynamic behavior are studied. Bifurcation diagrams with changing clearance value, friction coefficient, and driving speed are drawn. The research could provide important technical support and theoretical basis for the further study of the nonlinear dynamics of planar mechanism.